Design of Omniwheel Kinematics Learning Platform using ESP32 and Microsoft Visual Studio - Alamsyah, Sayyidul Aulia; Diptya Widayaka, Parama; Puspitaningayu, Pradini; Ikhsan, Taj Hakam; Arya Pradana, Rifando; Rizky Herdiansyah Palma, Ryan; Zuhayr Achmad, Ibrohim (BEST, 2025)
Wheeled robots have evolved significantly, starting from simple designs that utilized a single wheel for maneuvering to the present day, where there are numerous types capable of moving in all directions. The increasing complexity of wheeled robots today has created a learning gap for students who are just entering the world of robotics and the advanced robots that currently exist. Based on this problem, a mobile robot learning platform is needed to bridge their knowledge. The design of this platform is expected to help guide students’ learning of omniwheel robot kinematics in terms of robot model preparation, robot firmware design, communication design between the PC and the robot, and the implementation of kinematic formulas as robot commands. This platform is also designed to be universal, so it can be implemented for ready-made robots or robots built with any type of microcontroller. Comprehensive testing was performed for both movement modes in the application: forward kinematics and inverse kinematics. The forward kinematics test was carried out by assigning speed values to each motor individually. The inverse kinematics test was cariied out by assigning target position in cartesian plane. This platform is expected to serve as a valuable tool in the study of omniwheel robot kinematics.